Viability of Penicillium Citrinum on Different Carrier Media as Organic Fertilizer - Safinah Surya Hakim; Tri Wira Yuwati; Dony Rachmandi; Purwanto B Santosa; Adnan Ardhana; Dewi Alimah (Jurnal Wasian, 2019)
The use of bio-fertilizer is increasing along with the awareness of eco-friendly life style. The use of bio-fertilizer give several advantages such as enhancing plant growth, provide plant nutritions, easily absorbed by plant and environmental friendly. Endophytic fungi can be used as biological fertilizers.In this study, endophytic fungi Penicillium citrinum isolate P3.10 were used as a main ingredient for biological fertilizers. This study aims to investigate: (a) the most effective carrier material for biological fertilizers made from endophytic fungi P. citrinum and (b) maximum shelf-life of biofertilizers. Three carrier materials were tested to find out the best carrier as biological fertilizer carriers. Factorial Completely Randomized Design with two factors used in this study with the first factor is the type of carrier material (rice bran, saw dust, and peat soil), and the second factor is storage time (14, 28, 42, 56, dan 70 days).The result of the study and consideration based on the standards of biological fertilizer regulation of the Minister of Agriculture Number 70 / Permentan / SR.140 / 19/2011) showed that of the three tested carriers (rice bran, sawdust, and peat), peat showed the best performance as biofertilizer carrier with the recommend maximum shelf-life is 28 days (5,62 x 105 cfu/gram) due to its C/N ratio value and its viability to maintain the number of viable fungi. Keywords: formulation, biofertilizer, endophytic fungi, peat soil, shelf-life